The effect of virgin coconut oil foot massage on peripheral neuropathy in type 2 diabetes: A pre-experimental study - Yunita Liana; Raden Surahmat; Dedek Sartika; Yofa Anggriani Utama; Mareta Akhriansyah (Lentera Perawat, 2026)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels that can lead to diabetic peripheral neuropathy, presenting with pain, numbness, and foot ulcers. Foot massage therapy using Virgin Coconut Oil (VCO) may improve blood circulation, enhance nerve function, and support skin health due to its lauric and oleic acid content. Objective: This study aimed to examine the effect of foot massage therapy using virgin coconut oil on peripheral neuropathy scores among patients with type 2 diabetes mellitus. Methods: A pre-experimental one-group pretest–posttest design was conducted involving 30 patients with T2DM and peripheral neuropathy recruited through purposive sampling at a primary healthcare center. Peripheral neuropathy was assessed using the 10 g Semmes–Weinstein Monofilament Test before and after the intervention. Participants received three sessions of standardized foot massage using virgin coconut oil, each lasting 30 minutes. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. Results: Data from 30 participants were analyzed. The median peripheral neuropathy score significantly decreased from 6.00 ± 2.18 before the intervention to 2.00 ± 1.46 after the intervention (Z = –4.83, p < 0.001). The calculated effect size (r = 0.88) indicated a large and clinically meaningful effect, reflecting an improvement from moderate to mild neuropathy severity. Conclusion: Foot massage therapy using virgin coconut oil significantly reduced peripheral neuropathy severity in patients with type 2 diabetes mellitus. This intervention is safe, low-cost, and well tolerated, and it may serve as an effective complementary therapy for diabetic peripheral neuropathy management, particularly in low-resource settings.